Gross, histopathological and electronmicroscopic studies of canine mammary gland tumour treated with NS1 gene of canine parvo virus - VERMA, A K; JADON, N S; PANDEY, PRIYANKA; TIWARI, A K (The Indian Journal of Animal Sciences, 2014)
Female dogs (10) affected with mammary gland tumour (MGT) included in this study were treated with NS1 gene of canine parvo virus @ 200 µg intratumoural at weekly interval up to 4 week interval. Physical and clinical symptoms were noticed before and after treatment i.e at 0, first, second, third and fourth week of the treatment. The efficacy of the treatment was assessed on the basis of regression of tumour mass of mammary gland tumours, histopathological and electronmicroscopic (SEM and TEM) studies of biopsy samples of mammary tumour tissues. The parameters observed in this study revealed that the NS1 gene have apoptotic activity in regression of mammary gland tumours.